Effect of Mixed Layer Crystallinity on the Performance of Mixed Heterojunction Organic Photovoltaic Cells. (8th February 2014) - Song, Byeongseop; Rolin, Cedric; Zimmerman, Jeramy D.; Forrest, Stephen R.
<x xml:space="preserve">Abstract</x> Organic vapor‐phase deposition (OVPD) is used to grow tetraphenyldibenzoperiflanthen (DBP):C70 mixed heterojunction photovoltaic devices. Compared with vacuum thermal evaporation (VTE), the OVPD‐grown film develops nanocrystalline domains of C70. Optimized OVPD‐grown OPVs have a 61% fill factor for a 100 nm active layer thickness, whereas VTE‐grown devices have a 47% fill factor at the same thickness. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>